Carlo Isoardi, “Cristianesimo e antropologia. La promessa e la croce”, Giappichelli, Torino 2012, pp.185 - Massobrio, Francesco; Ristorto, Sonia (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)